Juniors` extreme risky behavior in the context of the structure of self-efficacy in competitive activity - Koval, I.; Yaremko, R.; Hurtovenko, N.; Sirko, R.; Stelmakh, O.; Slobodianyk, V.; Kulyk, Y.; Hoian, I. (Journal of Physical Education and Sport, 2024)
The aim of this study is to perform theoretical and empirical research on the manifestations, levels, and differences in extreme risky behavior among junior athletes within the framework of self-efficacy in competitive activities. Methods: The research participants consist of junior athletes who regularly compete at various levels and are enrolled in Ukrainian sports schools for children and youth. The study includes representatives from team contact sports such as football, handball, and fire-applied sports (n = 37; 50.00%) as well as individual contact sports including freestyle wrestling, karate, judo, Greco-Roman wrestling, and boxing (n = 37; 50.00%). Valid and reliable psycho-diagnostic tools, previously tested in numerous sports studies involving junior samples, were used to measure the relevant parameters. Results: Using the Kruskal-Wallis H-test, one significant superiority of the sample of junior athletes engaging in individual contact sports (Group 2) over the sample of junior athletes engaging in game contact sports (Group 1) by the parameter "emotional risk propensity" (H = 11.324; p < .001) was found. Eleven correlations were established, ten of them being direct and one correlation being inverse. It was found that the content parameters of junior athletes` extreme risky behavior are more dependent on self-efficacy than the functional parameters. It was explained that the content parameters - emotional, cognitive, behavioral, and controlling-regulatory propensities - are largely aimed at educational-training, competitive, and recovery activities. Attention was focused on the functional parameters, and it was explained that they reflected the juniors` psychophysiological activeness. It was empirically established and theoretically substantiated that the formedness of a medium level of extreme risky behavior (GII) has the largest number of significant superiorities. Discussion and conclusions: It was substantiated that the research into junior athletes` extreme risky behavior in the context of the structure of self-efficacy of competitive activity is an examination of correlations and significant differences of the relevant parameters pertaining to age-related psycho-physiological formations, the search for the meaning of life, lower self-confidence, and the formation of the worldviews which are inherent in adolescents. It was summarized that self-efficacy in interpersonal interaction, self-efficacy in subject activity, and motivation for achieving a sports result are relevant dimensions of junior athletes` sporting activities. It was recommended that a system of educational-training preparation aimed at optimizing junior athletes` extreme risky behavior should be developed. The obtained results possess scientific novelty and should be implemented in the educational-training activity of sports schools for children and youth.